Kinetic model of glycerol hydrodeoxygenation under inert conditions over copper catalyst. (2018) - Yfanti, V.L.; Ipsakis, D.; Lemonidou, A.A.
Abstract: A tandem catalytic cycle of methanol aqueous phase reforming–glycerol hydrodeoxygenation targeted to 1, 2-propanediol formation under inert conditions is presented. The elucidation of reaction pathways using in-situ IR technique showed that the first step of glycerol hydrodeoxygenation depends on hydrogen availability. Glycerol hydrodeoxygenation proceeds mainly via dehydration-hydrogenation route. However the simultaneous formation of 1, 2-propanediol via glyceraldehyde route, during the initial reaction time, could not be excluded. A Langmuir-Hishenwood type model best described the kinetics of the combined reaction cycle over a Cu:Zn:Al catalyst. The main reaction is the formation of 1, 2-propanediol, while C-C bond cleavage reactions are not favoured